Insecticides Cypermethrin and Chlorpyrifos Exposure: Effects on Sperm Motility and Fertility in Cyprinus carpio (Cypriniformes, Cyprinidae) - Argemi, Federico (2024)
The agricultural production of the Argentine Pampa is based on intensive cultures, and the most widely used insecticides correspond to cypermethrin (pyrethroid) and chlorpyrifos (organophosphate), among others. Sperm motility and fertility assessments are essential topics for biology and population dynamics studies on fish species. In this study the alterations of these endpoints after exposure to commercial formulation of both insecticides were used to analyze the effects on common carp sperm. After the in vitro exposure at nominal concentrations of 0.25, 0.5, 1, and 2 μg/L of cypermethrin, a significant reduction in motility in 0.5 μg/L concentrations was observed respect control group. The same nominal concentrations were tested for chlorpyrifos, and the same significative effect was detected at 2.0 μg/L. Fertilization rate was significantly reduced at concentrations from 0.5 μg/L cypermethrin exposure, and from 1.0 μg/L in the case of chlorpyrifos. Eggs LC50 / 24 h (95% confidence limit) exposed to cypermethrin was 0.57 μg/L (0.36 - 0.88), and exposed to chlorpyrifos was 2.45 μg/L (1.13-5.29). However, is still debatable how these insecticides impact on fish reproduction, using this in vitro scenario we found a clear reduction in sperm motility and fertility.